Amyloid β toxic conformer has dynamic localization in the human inferior parietal cortex in absence of amyloid plaques. Issue 1 (December 2018) - Kageyama, Yusuke; Saito, Atsushi; Pletnikova, Olga; Rudow, Gay; Irie, Yumi; An, Yang; Murakami, Kazuma; Irie, Kazuhiro; Resnick, Susan; Fowler, David; Martin, Lee; Troncoso, Juan
Abstract Amyloid β (Aβ) plays a critical role in the pathogenesis of Alzheimer's disease. Nevertheless, its distribution and clearance before Aβ plaque formation needs to be elucidated. Using an optimized immunofluorescent staining method, we examined the distribution of Aβ in the post-mortem parietal cortex of 35 subjects, 30 to 65 years of age, APOE ε3/ε3, without AD lesions. We used 11A1, an antibody against an Aβ conformer which forms neurotoxic oligomers. 11A1 immunoreactivity (IR) was present in cortical neurons, pericapillary spaces, astrocytes and the extracellular compartment at 30 years of age. The percentage of neurons with 11A1 IR did not change with age, but the number and percentage of astrocytes with 11A1 IR gradually increased. Notably, the percentage of pericapillary spaces labeled with 11A1 IR declined significantly in the 5th decade of the life, at the same time that 11A1 IR increased in the extracellular space. Our findings indicate that the Aβ toxic conformer is normally present in various cell types and brain parenchyma, and appears to be constitutively produced, degraded, and cleared from the inferior parietal cortex. The decrease in pericapillary Aβ and the concomitant increase of extracellular Aβ may reflect an age-associated impairment in Aβ clearance from the brain.